Dynamic network performance evaluation of general insurance companies: an insight into risk management committee structure - Kuo K.-C.; Kweh Q.L.; Ting I.W.K.; Azizan N.A. (Routledge, 2023)
Nowadays, insurance companies are operating in a challenging and borderless business world. They should focus on improving their competitive advantages to secure increased profits and reduced costs. As fundamental elements of total quality management, performance measurement and risk management play important roles in ensuring sustainable operation. This study investigates the relationship between risk management committee structure and the operating efficiency of general insurance companies operating in Malaysia for the period 20082013. First, this research applies the dynamic network data envelopment analysis methodology, decomposing the typical two-stage operating process of general insurance companies. That is, we estimate the marketing efficiency and profitability efficiency. We find that the sample companies have to first improve their marketing efficiency, and then proceed to improve their profitability efficiency. Second, this study applies truncated regression to test the impact of risk management committee structure on general insurers operating efficiency. In today's business world, general life insurance companies have to manage risks well to gain a competitive advantage. 2015 Taylor & Francis.